Character Education: Comparison Analysis Between The Thinking of Ki Hajar Dewantara and Abdullah Nasih Ulwan - Kasmuri Selamat; Adripen Adripen; Jamaluddin Jamaluddin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This research was inspired by the fact that the affective domain has not become a priority scale and is a serious concern of the three domains (cognitive, affective, and psychomotor) in the teaching and learning process in schools. The purpose of this research was to describe the biography, work, and character education of Ki Hajar Dewantara and Abdullah Nasih Ulwan This research was library research. The data was collected by finding some relevant sources. The collected data was analyzed by comparing the sources concerning the three issues. In conculusion, both figures had different biography, work, and character education. But they also had same way of thinking concerningcharacter education.